2017
DOI: 10.2109/jcersj2.16187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the Soret effect in a CaSiO<sub>3</sub> glass melt

Abstract: The mole fraction distributions of CaO and SiO 2 under a temperature gradient in a CaSiO 3 melt were calculated by molecular dynamics. The temperatures at the cold and hot ends of the gradient were 1800 and 2200 K, respectively, in the simulation. We used two sets of potential parameters proposed by Matsui et al. and Seo et al. The simulation results obtained with the two potentials indicate that the mole fraction of CaO in the cold region was higher than that in the hot region, and the mole fraction of SiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The simulation method was similar to that in our previous report 20 , but the details had some differences. We employed the potential proposed by Seo 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The simulation method was similar to that in our previous report 20 , but the details had some differences. We employed the potential proposed by Seo 21 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the case of a soda (Na 2 OSiO 2 ) glass, the average coordination number of O around Si is four, which is determined from the first plateau of the SiO curve in such RCN plot. 17) From the experimental results, it was reported that the coordination number of boron changes with the addition of Al. 24) The average coordination numbers of boron in the BO bond were calculated to be 3.65 and 3.62 for the CTBK and CTBKA glasses, respectively, and from these values, the three-coordinated (B 3 ) and four-coordinated boron (B 4 ) was estimated to be 35.1 % (B 3 ) and 64.9 % (B 4 ) for CTBK, and 38.1 % (B 3 ) and 61.9 % (B 4 ) for CTBKA.…”
Section: Effects Of Al 2 Omentioning
confidence: 99%
“…The advantage of the MD in the study of the Soret effect is that the effect of the natural convection and Marangoni convection can be neglected since the effect of gravity and no boundary can be excluded. 26) The author and coauthors compared the Soret coefficient calculated by nonequilibrium molecular dynamics (NEMD) with that by adjusted Kempers mode [Eq. (12)] 17) in the CaOSiO 2 melts.…”
Section: Verification With Numerical Simulationmentioning
confidence: 99%